Queer Dickens erotics, families, masculinities - Furneaux, Holly (Oxford : Oxford University Press, 2009)
Furneaux offers a new reading of Dickens. She argues that rather than representing a largely conventional view of sexuality and gender his corpus is distinctly queer, displaying a fascination with the diversity of gender roles, the expandability of notions of the family and the multiplicity of sexual desire.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Dickens, Charles, -- 1812-1870 -- Criticism and interpretation; Queer theory; Gender identity in literature; Sex role in literature